CONTRACTUALISTIC MEASUREMENTS OF THE GENDER: POSSIBILITIES AND BORDERS - D. V. Usov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The purpose of the study is critical reconstruction of gender issues within the framework of modern political philosophy and political anthropology, in-depth reflection of the phenomena of justice, identity, human dignity in the aspect of their gender measurements and the search for the answer to the fundamental question for leading gender discourses: is freedom and justice, in fact, possible only together with stresses, a feeling of one’s sense-rooted belonging to one or another community? Theoretical basis. The supplement of the phenomenological and transcendental methodology by the method of contractualism directs the study of the topic specified in the article’s title into a new direction, and reflects its essential measurements and aspects. Understanding gender as an important philosophical and anthropological problem and a complex "social construct" precisely within the framework of the latest critical and self-critical versions of the theory of social contract reveal fruitful perspectives for political philosophy and anthropology. Originality. The study of the phenomena of "recognition" (A. Honneth) of "gender justice" (N. Fraser), "moral sense" (E. Tugendhat) outlines the possibilities and sense of filling the principle of social contract with a specific theoretical and practical content, substantiates the need to expand the philosophical and anthropological interpretation space of gender issues. Conclusions. Significance of the gender community for the sociocultural and existential identity of the individual enables (through organic, life-world belonging to a certain tradition and culture) his/her security and the ability to adequately orient in difficult life situations. However, the main purpose of human life is the ability to self-identity, even after profound changes in the structure of personality that arise in difficult situations of contempt and injustice.